Microcosm Biofilm Formation on Titanium Surfaces - Dal’Agnol,Claudio Zeferino (2015)
Risk factors associated with peri-implantitis are related to the biofilm composition around the implant and the ability of bacterial adhesion. This study evaluated the biofilm formation on different surfaces of commercially pure titanium (CP Ti) grade 4 after 12, 24, 48 and 168 hours using the microcosm technique and scanning electron microscopy (SEM). The following surface conditions were examined: S (control)- smooth and plain; B- sand-blasted with aluminum oxide; E- etched using nitric acid; and BE- the combination of J and A treatments. Statistical differences on biofilm formation (CFU/ mg) were found between the control (S) and B surfaces at the first 12 hours, which are related to the lowest (Ra = 0.21 µm) and highest (Ra = 0.62 µm) mean roughness values. At 168-hour all surfaces showed similar biofilm formation. Yet, microbial growth occurred on all surfaces, regardless of the surface treatment.